1970
DOI: 10.1128/jb.101.1.278-285.1970
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscopic Observations on the Effects of Penicillin on the Morphology ofChlamydia psittaci

Abstract: L ceRs were infected at high multiplicity with meningopneumonitis organisms and incubated in medium containing 200 units per ml of penicillin. At intervals up to 48 hr after infection, cells were removed and thin sections were prepared for electron microscopic studies on the morphology of the developing organism. Penicillin had no effect on the initial reorganization of the infecting elementary body to form the developmental reticulate body (RB), and, up to 12 hr after infection, the treated and untreated cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
111
0
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(119 citation statements)
references
References 12 publications
7
111
0
1
Order By: Relevance
“…It should be noted, that in the latter study, chlamydial persistence was not demonstrated using the characteristic features now associated with the morphology of persistent chlamydial infections. Detailed description of electron microscopic observations on the effects of penicillin on the morphology of Chlamydia psittaci Cal10 in L cells showing aberrant chlamydial stages were published by Matsumoto and Manire [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted, that in the latter study, chlamydial persistence was not demonstrated using the characteristic features now associated with the morphology of persistent chlamydial infections. Detailed description of electron microscopic observations on the effects of penicillin on the morphology of Chlamydia psittaci Cal10 in L cells showing aberrant chlamydial stages were published by Matsumoto and Manire [13].…”
Section: Discussionmentioning
confidence: 99%
“…Persistent forms of Chlamydia trachomatis and Chlamydia pneumoniae are well described by their characteristic electron microscopic appearance [2,13,14]. Thus, chlamydial ultrastructure in single and co-infected cells was compared by transmission electron microscopy (TEM).…”
Section: Co-infection With Ca-pedv Induced Ultrastructural Morphologimentioning
confidence: 99%
“…Furthermore, treatment of L2-infected S2 cells with penicillin resulted in enlarged RBs (unpubl. data), similar to the changes reported in mammalian cells (Matsumoto and Manire, 1970;Kramer and Gordon, 1971). The fact that IncG was produced and localized to the inclusion suggests that Chlamydia was metabolically active and modified the inclusion as it does during mammalian infection.…”
Section: U Cdc42 Rho1mentioning
confidence: 99%
“…Penicillin-exposure inhibited C. psittaci RB to EB conversion, forming greatly enlarged, irregular, less electrondense RB (i.e. AB) that shed membrane blebs [5]. Amoxicillinexposed, Chlamydia muridarum-infected murine epithelial cells show the characteristic AB morphology (Fig.…”
Section: Introductionmentioning
confidence: 99%